Faktor Risiko Lingkungan Fisik Rumah dan Karakteristik Wilayah Sebagai Determinan Kejadian Penyakit Tuberkulosis Paru di Wilayah Kerja Puskesmas Sentani Kabupaten Jayapura Provinsi Papua - Andreas Christian Ayomi; Onny Setiani; Tri Joko (Master Program of Environmental Health, Faculty of Public Health, Diponegoro University, 2012)
Background: Lung Tuberculosis is caused by pathogen bacteria Mycobacterium tuberculosis and has infected a third of the world population. The incidence of Pulmonary Tuberculosis in industrialized countries for the last 40 years indicates that prevalence rate is very small, whereas 95% of the sufferers in developing countries are approximately 8 million people. They are infected by Pulmonary Tuberculosis with 3 million of death rate per year. Pulmonary Tuberculosis in Indonesia according to WHO (1999 and 2004), is as many as 583,000 cases: 140,000 for death and 13/100.000 people are new patients. Papua province in 2007 has the number of new patients with smear Basil (BTA) (+) amounting 1535 patients, more than half of the patients are those who are between 15-45 years of age or equal to 933 cases. If such a condition continues, Papua Province will lose productive human resources. Methods: This research was aimed to determine risk factors of physical environment in housing and regional characteristics of pulmonary tuberculosis in the working area of Public Health Centre, Sentani, Jayapura Regency, Papua Province. Type of the study was an observational study with case control approach. Subjects of the research were 106 respondents, consisting of 53 cases and 53 controls. Statistical analysis was done by Chi-square test, the relationship of risk factors with the occurrence of tuberculosis (by using univariate and bivariate analysis), and then multivariate analysis with logistic regression test. Results: The result of bivariate analysis showed that there is a relationship between factors type of house (p = 0,031), natural lighting (p = 0.004), the existence among of direct sunlight (p = 0.020), house ventilation (p = 0.020), bedroom ventilation (p = 0.003), humidity of bedroom (p = 0.000), temperature of bedroom (p = 0.000), house density (0,004), and type of house floor (0.001), whereas the result of multivariate analysis shows that risk factors for pulmonary tuberculosis is bedroom ventilation (OR = 16.949), temperature of bedroom (OR = 8.913), and type of house floor (OR = 4.575), and as protective factor is house ventilation (OR = 0.036). Conclusions: In this research, all of variables studied have significant relationships and 3 variables which are risk factors for the occurrence of tuberculosis, namely, bedroom ventilation, temperature of bedroom, and type of house floor. Key words: Pulmonary Tuberculosis, Environmental Characteristics, Regional Characteristics.